Global data on earthworm abundance, biomass, diversity and corresponding environmental properties - Helen R. P. Phillips (Scientific Data, 2021)
Measurement(s) earthworm communities • Abundance • organic material • Diversity • environmental properties Technology Type(s) digital curation Factor Type(s) location Sample Characteristic - Organism Lumbricina Sample Characteristic - Environment soil Sample Characteristic - Location global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13399118